Combatting the rising costs of cancer drugs; interventions from a university hospital’s perspective - Dane, Aniek; van Leeuwen, Roelof; Hoedemakers, Maaike; van der Kuy, Hugo; Sleijfer, Stefan (Frontiers in Pharmacology, 2023)
Rapid increase in cost continues to have negative impact on patients’ accessibility to life-changing anticancer medications. Moreover, the rising cost does not equate to similar increase in medication effectiveness. We recognise our responsibility as a university hospital to tackle this imbalance and strive to provide high quality, sustainable, affordable and accessible care. An active approach in cost containment of expensive and innovative cancer drugs was adopted in our organisation to safeguard accessibility and improve quality of life for patients. In this article, we described four inverventions: 1) identify right patient and minimise overtreatment, 2) in-house medicine production for selected indications, 3) minimise medicine spillages and 4) effective procurement strategies. We call on other hospitals to take action and, favourably, to collaborate on a European level. Together, we will safeguard the current of future care of our patients.